THE INVISIBILITY OF A GAZE - Gomes, Ana Paula de Oliveira; Matias, Ana Paula de Lima; dos Santos, Sara Gomes (Editora Impacto Científico, 2025)
This essay was developed based on the reading of the Law of Guidelines and Bases of Education (LDB) and on student (and teacher) experiences derived from a concrete case. In general terms, the work aims to discuss the eloquent silence of Law 9.394/1996 regarding blind or visually impaired persons. Through bibliographic research methods, the following specific objectives are articulated: a) to understand the system of protection of human duties; b) to contextualize the relevance of the Marrakesh Treaty; and c) to document the omission of the LDB in terms of the inclusion of blind or visually impaired teachers and students. The study is justified by the need to weave dialogues between sources in favor of education and work. The invisibility of the blind person in education implies unjustifiable obstacles to insertion into the world of work. Unfortunately, what should exist in Brazil does not. There is a lack of otherness toward people with disabilities. The person must always come before their limiting conditions.DOI: https://doi.org/10.56238/edimpacto2025.083-002